The application of automated mine survey systems to mine surveying practice - Ketteman, Mark Robert (1985)
Mine surveying is at present undergoing a revolution with the possibility of fully automating survey tasks. This has become possible because of the introduction of automated systems of data measurement, acquisition, processing and plotting.